2020
DOI: 10.2147/tcrm.s249116
|View full text |Cite
|
Sign up to set email alerts
|

<p>Health-Related Quality of Life in Patients After Surgically Treated Midface Fracture: A Comparison with the Croatian Population Norm</p>

Abstract: Aim: To evaluate the health-related life quality of patients after surgically treated midface fractures. Patients and Methods: This retrospective cohort study compared the 36-Item Short Form Health Survey (SF-36) scores of 42 male patients following surgically treated maxillary or zygomatic fractures with the reported normative data of the SF-36 for the Croatian population. Results: The current study showed that the health-related life quality of surgically treated patients was comparable to similar age, gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(52 reference statements)
0
1
0
1
Order By: Relevance
“…Time period was a significant determinant of patient life quality in a cohort study by Lupi-Ferandin et al However, the mean difference in quality of life after follow up period was not investigated. 27 Another study by Boljevic et al reported an intriguing finding in which a considerable number of patients (40%) reported no improvement in quality of life six months after surgery. It was mostly attributed to pain, appearance, and mood issues during postoperative period.…”
Section: Discussionmentioning
confidence: 96%
“…Time period was a significant determinant of patient life quality in a cohort study by Lupi-Ferandin et al However, the mean difference in quality of life after follow up period was not investigated. 27 Another study by Boljevic et al reported an intriguing finding in which a considerable number of patients (40%) reported no improvement in quality of life six months after surgery. It was mostly attributed to pain, appearance, and mood issues during postoperative period.…”
Section: Discussionmentioning
confidence: 96%
“…A composição do terço médio facial é dada pelos ossos: maxila, zigomático, nasal, palatino, vômer, lacrimais e concha nasal inferior, em articulação com os ossos do crânio: temporal, frontal, esfenóide e etmóide e apresentam estruturas anatômicas com grande importância funcional como o nariz e o globo ocular (MEUTEN et al, 2015). Além disso a posição proeminente dessa região implica diretamente na estética facial do paciente e no seu bem estar social e psicológico (LEVINE et al, 2005;LUPI-FERANDIN et al, 2020).…”
Section: Introductionunclassified